THE EFFECT OF HYDROCOLLOID PROPHYLAXIS IN PREVENTING MEDICAL ADHESIVE-RELATED SKIN INJURY (MARSI) IN CHILDREN WITH ENDOTRACHEAL TUBES IN THE PEDIATRIC INTENSIVE CARE UNIT - Juanda Mutifa; Nani Nurhaeni; Robiyatul Adawiyah (rifascholarpublisher.com, 2026)
Background: Endotracheal tube (ETT) insertion is a common therapy for critically ill children in the pediatric intensive care unit (PICU). Medical adhesives used to secure the ETT may compromise skin integrity, leading to medical adhesive-related skin injury (MARSI). Preventive strategies are needed to reduce the risk of MARSI in pediatric patients. Objective: This study aimed to examine the effect of hydrocolloid prophylaxis in preventing MARSI in children with ETT in the intensive care unit. Methods: A one-shot case study design was used involving 15 pediatric patients with ETT in the intensive care unit. Hydrocolloid prophylaxis was applied to prevent skin injury caused by medical adhesives. Data were analyzed to determine the occurrence of MARSI after the intervention. Results: The findings showed that only two out of 15 respondents experienced MARSI, with a statistically significant result (p = 0.001; p < 0.05). Conclusion: Hydrocolloid prophylaxis was effective in preventing MARSI in children with ETT. The use of this prophylactic intervention is recommended for implementation by nurses in the pediatric intensive care unit.